2011
DOI: 10.5539/ijbm.v6n7p181
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Customer Knowledge on CRM Performance of Malaysian ICT Companies: A Structural Equation Modeling Approach

Abstract: The business environment is transforming from product-centric to customer-centric. CRM as a customer-oriented business approach is considered as one of the powerful capabilities in organizations which help them to transform themselves to a customer-centric environment. The objective of the studies to configure the constructs of customer knowledge and CRM performance among 201 ICT companies in Malaysia. This study also examines the influence of customer knowledge as exogenous variable on CRM performance as endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Previous studies have confirmed how effective knowledge-management processes will determine CRM performance (e.g., Campbell, 2003;Croteau and Li, 2003;Nejatian et al, 2011). Campbell (2003 empirically observed the importance of harnessing knowledge-based competences when implementing CRM, because this accumulated knowledge enables firms to develop customer-specific strategies, which can become a source of competitive advantage.…”
Section: The Impact Of Knowledge Management Processes In Crm Performancementioning
confidence: 87%
See 3 more Smart Citations
“…Previous studies have confirmed how effective knowledge-management processes will determine CRM performance (e.g., Campbell, 2003;Croteau and Li, 2003;Nejatian et al, 2011). Campbell (2003 empirically observed the importance of harnessing knowledge-based competences when implementing CRM, because this accumulated knowledge enables firms to develop customer-specific strategies, which can become a source of competitive advantage.…”
Section: The Impact Of Knowledge Management Processes In Crm Performancementioning
confidence: 87%
“…Since knowledge management is responsible for acquiring and accumulating knowledge within organizations to promote innovation and CRM is able to capture customer preferences, desires and above all, accumulate knowledge; the integration of these two concepts could provide significant benefits to organizations (Nejatian et al, 2011). Consequently, these findings are also valuable for academics who study the business value of IT-related innovations.…”
Section: Relations To Previous Findings and Concluding Remarksmentioning
confidence: 95%
See 2 more Smart Citations
“…Specifically, the values indicate that the CKM dimensions and knowledge sharing have high internal consistency (knowledge for customer (0.80), knowledge about customer (0.81), knowledge from customer (0.89) and knowledge sharing (0.82)). Previous study by Nejatian et al (2011) also found that CKM dimensions have very high internal consistency (Knowledge for Customers = 0.95, Knowledge about Customers = 0.97 and Knowledge from Customers = 0.96) and 0.88 for knowledge sharing (Kang, Kim & Chang, 2008). Thus, the internal consistency reliability of these measures can be considered as good.…”
Section: Profile Of Respondentsmentioning
confidence: 87%